Stromal Osseous Metaplasia in Ovarian Serous Cystadenocarcinoma - Doaa A. Alghamdi; Layla S. Abdullah; Ahmed A. Mousa; Sumiah A. Shinawi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Ovarian ossification is a rare pathological condition that may be encountered in neoplastic as well as in non-neoplastic contexts. Its etiology and pathogenesis are controversial. We report the case of a 33-year old female (P6 + 1) who presented with a 4 month history of abdominal distention and amenorrhea. Radiological investigations showed complex pelviabdominal mass with foci of calcification. The patient underwent total hysterectomy with bilateral salpingo-oophorectomy. Gross pathology findings showed bilateral enlargement of the ovaries and gritty sensation of ovary in slicing. Microscopic pathology showed mature lamellate bone in the wall of right ovary invaded by serous neoplastic cells.